2011
DOI: 10.1051/alr/2011105
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic of intoxication and detoxification in juveniles ofMytilus chilensis(Bivalvia: Mytilidae) exposed to paralytic shellfish toxins

Abstract: -Juveniles of the mussel Mytilus chilensis were exposed to a diet containing paralytic shellfish poisoning (PSP) toxins produced by the dinoflagellate Alexandrium catenella (strain ACC02). The feeding behaviour and the dynamics of intoxication and detoxification were evaluated over an intoxication period of nine days, followed by a detoxification period of eight days. A significant reduction in the feeding activity was measured during the first days of exposure to the PSP toxins (days 0 and 2), followed by a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Thus, in addition to accuracy and reproducibility, the establishment of the long-term primary culture of bivalve hemocytes also confers a more sensitive assay to demonstrate the impact of any environmental pollutants and inductors, via regulation of hemocyte function after several hours’ exposure. Future usage of cell cultures could also clarify the mechanisms used by M. chilensis to bioaccumulate high concentrations of toxins, unlike other bivalves, such as oysters [ 28 , 54 ]. Additionally, by using primary cell cultures of hemocytes, early biomarkers of pollution could be identified and subsequently used in sentinel organisms, such as M. chilensis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in addition to accuracy and reproducibility, the establishment of the long-term primary culture of bivalve hemocytes also confers a more sensitive assay to demonstrate the impact of any environmental pollutants and inductors, via regulation of hemocyte function after several hours’ exposure. Future usage of cell cultures could also clarify the mechanisms used by M. chilensis to bioaccumulate high concentrations of toxins, unlike other bivalves, such as oysters [ 28 , 54 ]. Additionally, by using primary cell cultures of hemocytes, early biomarkers of pollution could be identified and subsequently used in sentinel organisms, such as M. chilensis .…”
Section: Discussionmentioning
confidence: 99%
“…Studies using M. chilensis exposed to Alexandrium catenella have shown that this species is capable of a rapid response and has a great capacity for toxin acclimation. The mussel M. chilensis is of particular interest given its ecological and commercial importance to the Austral Region of Chile, where over 180,000 tons are annually produced through suspended cultivation and where HABs are very frequent [ 28 ]. Therefore, M. chilensis could be a good model to study the effects of STX on hemocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The soft-shell clam, Mya arenaria, and the blue mussel, Mytilus edulis, are two of the most abundant species (Beal et al, 2001;Thelen and Thiet, 2009). Both clams and mussels readily ingest toxic Alexandrium fundyense and accumulate PST within their tissues (Shumway et al, 1988;Bricelj et al, 1990;Moroñ o et al, 2001;Bricelj et al, 2005;Navarro et al, 2011). The clam, via kairomone and feeding-related cues, increases PST production in A. fundyense.…”
Section: Broader Implications: Impact Of Community Composition Upon Imentioning
confidence: 99%
“…It is, therefore, no surprise that mussels such as P. canaliculus feed readily on toxic dinoflagellates and toxin concentrations accumulate in their tissues (Shumway and Cucci 1987;Marsden and Shumway 1992;Navarro et al 2008Navarro et al , 2011Navarro and Contreras 2010). In some of these studies, clearance rates recorded using high concentrations of toxic algae may have been depressed initially, but resumed to normal levels following a few days of exposure.…”
Section: Clearance and Excretion Ratesmentioning
confidence: 99%
“…Numerous studies have investigated the effects of PSP dinoflagellates on mussels and some species can maintain clearance rates on exposure to toxic algae, although it may take a short acclimation period to adjust to the diet (Navarro et al 2011). The green-lipped mussel (Perna canaliculus) was selected for study because early research showed that it feeds and accumulates PSTs in its tissues (Marsden and Shumway 1992), and is regularly tested as part of the nation-wide biotoxin-monitoring program.…”
Section: Introductionmentioning
confidence: 99%